Eating in groups: Do multiple social influences affect intake in a fast-food restaurant?. (May 2015) - Brindal, Emily; Wilson, Carlene; Mohr, Philip; Wittert, Gary
This study investigated multiple social influences to determine whether they affect amount eaten at a fast-food environment. Using observational methods, data on meal duration, foods eaten and personal characteristics were collected for 157 McDonald's patrons. Analysis of covariance revealed that female diners ate less kilojoules when eating in mixed- versus same-sex groups (adjusted difference = 967 kJ, p  < .05), while male diners eating in mixed-sex company ate more in groups compared to pairs (adjusted difference = 1067 kJ, p  = .019). Influences to increase and restrict the amount eaten can operate simultaneously in an eating environment with gender a critical factor for consideration.